PEMBANGUNAN PASAR SEHAT KRAMATMULYA DESA KELAPA GUNUNG KABUPATEN KUNINGAN SEBAGAI OPTIMALISASI POTENSI UMKM - Darto, Darto; Aditiany, Savitri; Fauzi, Muhammad Rifqi (Majalah Ilmiah UNIKOM, 2025)
Due to its rich natural resources, Kramatmulya District is home to a wide variety of food and local specialty products. This abundance has led to approximately 2,003 micro, small, and medium enterprises (MSMEs) conducting trade to support their livelihoods and supply the community's food needs. Despite this, these MSMEs have encountered difficulties, such as a shortage of skilled labor, antiquated production infrastructure, outdated marketing approaches, and a 30% decline in revenue during the COVID-19 pandemic. This "healthy market" initiative aims to enhance these MSMEs and strengthen the village economy, contributing to Kuningan Regency's broader vision and mission, including the realization of the "Pinunjul Village." The study utilized a qualitative descriptive approach, with informants chosen via purposive sampling. Guidelines from Ministry of Health Decree No. 519 govern the execution of this healthy market project. Successful development and training of the healthy market will facilitate the achievement of Kuningan Regency's vision and mission. Key Words: development of village healthy markets; digital marketing; micro small and medium enterprises; village development